Effect of Glass Bottle Waste and Granite Waste as Coarse Aggregate Substitutes on the Compressive Strength of Normal Concrete - Arif Rahman Hakim; Agyanata Tua Munthe (Marasofi International Media and Publishing (MIMP), 2025)
The increase in waste from construction and daily human activities has raised environmental concerns, particularly the disposal of non-biodegradable materials such as glass and granite. This study investigates the potential use of glass bottle waste and granite waste as partial substitutes for coarse aggregates in normal concrete. The objective is to evaluate their influence on the compressive strength of concrete with a target strength of 20 MPa. Experimental tests were conducted using cylindrical specimens (15 cm × 30 cm), incorporating 3% glass waste and varying granite waste contents (3%, 5%, 8%, and 10%). A total of 45 specimens were tested at curing ages of 7, 14, and 28 days. The results show that the highest compressive strength of 25.20 MPa was achieved with 3% glass and 3% granite waste, surpassing the design strength. However, increasing granite content beyond 3% led to a gradual strength reduction. The findings indicate that limited substitution of both wastes is feasible without compromising structural performance. Future research should optimize mix design parameters to improve efficiency and explore higher substitution levels for environmental sustainability.